A method for preparing high-strength and tough nanocomposite hydrogel

By introducing polymers and two-dimensional nanosheets into the hydrogel to form a nano-confined space, and forming neatly arranged layered PVA crystallization zones through salting and water washing treatment, the problem that existing hydrogels cannot have both high moisture content and high mechanical properties is solved, and hydrogel preparation with high moisture content and high mechanical properties is achieved.

CN116478491BActive Publication Date: 2025-03-18BEIHANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310501734.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-06
Publication Date
2025-03-18
Estimated Expiration
2043-05-06

AI Technical Summary

Technical Problem

The existing hydrogels have shortcomings in both high moisture content and high mechanical properties, and cannot significantly improve the strength and fracture toughness of the hydrogel.

Method used

By introducing polymers and two-dimensional nanosheets into the hydrogel, a nano-confined space is formed, and neatly arranged layered PVA crystallization zones are formed through salting and water washing treatment, protecting the crystallization zone from being destroyed, thereby improving the mechanical properties of the hydrogel.

Benefits of technology

The high moisture content and high mechanical properties of the hydrogel are achieved, with tensile strength up to 23.6±1.1MPa, elongation at break as high as 1278±90%, and toughness in water as high as 115.0±10.1MJ m-3.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116478491B_ABST
    Figure CN116478491B_ABST
Patent Text Reader

Abstract

The present invention relates to a high-strength and tough nanocomposite hydrogel and a preparation method thereof, which belongs to the technical field of hydrogel preparation and solves the problem that the existing hydrogel cannot have both high water content and high toughness. The hydrogel contains polymers and two-dimensional nanosheets, the polymers are distributed in any area in the hydrogel, and the two-dimensional nanosheets are oriented and arranged in the hydrogel; wherein a nano-confined space is formed between adjacent two-dimensional nanosheets, and a layered PVA crystal region is contained in the nano-confined space. The preparation of a hydrogel with both high water content and high mechanical properties is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogel preparation, and in particular to a method for preparing a high-strength and tough nano composite hydrogel. Background Art

[0002] Traditional hydrogels generally have poor mechanical strength, significantly lower than the mechanical properties of many natural biological tissues, such as tendons, ligaments and menisci. They also lack the ordered and dynamic structure of biological soft tissues, which limits the widespread application of synthetic hydrogels.

[0003] To solve this problem, a variety of methods have been tried to improve the mechanical properties of hydrogels, such as using multiple polymer network design strategies to improve the mechanical properties and toughness of gels; using directional freezing to prepare CNF / PVA hydrogels, which have good mechanical properties; using mechanical stretching to prepare PVA hydrogels, which have a high fatigue threshold (1250J / m 2 ); for example, the mechanical properties of PVA hydrogel were adjusted by salting-out method.

[0004] However, these strategies do not significantly enhance the strength and fracture toughness of hydrogels, but only improve them in certain directions or enhance their properties by forming additional excess crystalline regions, which reduces their original high water content.

[0005] In summary, the existing hydrogel preparation methods cannot obtain hydrogels with high water content and high strength. Summary of the invention

[0006] In view of the above analysis, the embodiments of the present invention aim to provide a high-strength and tough nanocomposite hydrogel and a preparation method thereof, so as to solve the problem that the existing hydrogels cannot have both high water content and high strength.

[0007] On the one hand, an embodiment of the present invention provides a high-strength and tough nanocomposite hydrogel, wherein the hydrogel contains polymers and two-dimensional nanosheets, wherein the polymers are distributed in any area of ​​the hydrogel, and the two-dimensional nanosheets are oriented and arranged in the hydrogel;

[0008] Wherein, a nano-confined space is formed between adjacent two-dimensional nanosheets, and a layered PVA crystal region is contained in the nano-confined space.

[0009] Based on the further improvement of the above hydrogel, the polymer includes polyvinyl alcohol and calcium alginate.

[0010] Based on the further improvement of the above hydrogel, the two-dimensional nanosheets include graphene oxide or montmorillonite.

[0011] On the one hand, an embodiment of the present invention provides a method for preparing a high-strength and tough nanocomposite hydrogel, comprising:

[0012] Step 1: preparing a hydrogel with nanoconfined space;

[0013] Step 2: salting out and washing the hydrogel to obtain a high-strength and high-toughness nanocomposite hydrogel;

[0014] The hydrogel contains neatly arranged two-dimensional nanosheets, and nano-confined spaces are formed between adjacent two-dimensional nanosheets. After salting out and hydrolysis treatment, a hydrogel containing layered PVA crystal regions in the nano-confined spaces is obtained.

[0015] Based on the further improvement of the above preparation method, when the hydrogel with nano-confined space is treated by salting out, the polymer crystallizes;

[0016] Wherein, a layered PVA crystal region is formed in the nano-confined space, and a randomly arranged peripheral crystal region is formed outside the nano-confined space.

[0017] Based on the further improvement of the above preparation method, when the hydrogel after salting out is washed with water, the PVA crystallization region within the nano-confined space is not destroyed, and the peripheral crystallization region outside the nano-confined space is destroyed.

[0018] Based on the further improvement of the above preparation method, in the step 1, it includes:

[0019] S101: preparing an auxiliary forming hydrogel, and placing the auxiliary forming hydrogel in water to swell to saturation;

[0020] S102: placing the auxiliary forming hydrogel swollen to saturation into a solution that is immiscible with the hydrogel;

[0021] S103: preparing a spreading solution, and continuously dropping the spreading solution onto the surface of the auxiliary forming hydrogel to perform super spreading and interfacial film-forming reaction, so as to obtain a hydrogel film on the surface of the auxiliary forming hydrogel;

[0022] S104: transferring the hydrogel film to a solid surface, peeling it off from the solid surface after drying, and immersing it in water again to obtain a hydrogel with nano-confined space.

[0023] Based on the further improvement of the above preparation method, the spreading solution is a mixed aqueous solution including two-dimensional nanosheets, polyvinyl alcohol, and sodium alginate;

[0024] Wherein, the two-dimensional nanosheets include graphene oxide or montmorillonite, and the content of the two-dimensional nanosheets in the spreading liquid is 0.1-20wt%;

[0025] The total content of the polyvinyl alcohol and sodium alginate in the spreading liquid is 80%-99.9wt%;

[0026] The ratio of polyvinyl alcohol to sodium alginate is 2 to 16:1.

[0027] Based on the further improvement of the above preparation method, the two-dimensional nanosheet is graphene oxide, and the content of the graphene oxide in the spreading solution is 0.24-1.9wt%, preferably 0.58wt%.

[0028] Based on the further improvement of the above preparation method, in step 2, the hydrogel is immersed in a salt solution for salting out, and then immersed in deionized water to wash away the salt, and the steps of immersing in a salt solution and then immersing in deionized water to wash away the salt are repeated to obtain a high-strength and tough nano-composite hydrogel; preferably, the number of times the hydrogel is salted out and washed with water is 5 times.

[0029] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0030] 1. The present invention uses two-dimensional nanosheets as nanofillers, adds a small amount of nanofillers to the hydrogel, forms nanoconfined spaces between the nanofillers, gathers a small amount of polymers in the nanoconfined spaces, and due to the low content of the nanofillers, most of the polymers are located outside the nanoconfined spaces. During salting out, a crystallization region is generated anywhere in the hydrogel, wherein neatly arranged layered PVA crystallization regions are formed in the nanoconfined spaces, and randomly arranged peripheral crystallization regions are formed in other parts. After washing, the crystallization regions outside the nanoconfined spaces are destroyed, so the water content of the hydrogel is increased. At the same time, the nanoconfined space protects the crystallization regions formed therein, so that the layered PVA crystallization regions in the nanoconfined space will not be destroyed. Compared with the randomly arranged peripheral crystallization regions, the mechanical properties of the hydrogel are improved, thereby realizing the preparation of a hydrogel with both high water content and high mechanical properties.

[0031] 2. The super-spreading technology is used to prepare the hydrogel, so that a small amount of two-dimensional nanosheets are oriented and arranged in the hydrogel, and a nano-confined space is formed between adjacent two-dimensional nanosheets. During multiple salting-out and water-washing treatments, a layered PVA crystallization region is formed in the nano-confined space, and the nano-confined space is used to protect the crystallization region to avoid the destruction of the crystallization during the water-washing process. At the same time, multiple salting-out treatments can achieve a superimposed improvement in crystallinity. During the multiple salting-out and water-washing treatments, the mechanical properties of the hydrogel are superimposedly increased.

[0032] 3. By utilizing the nano-confined space between adjacent two-dimensional nanosheets, a hydrogel with a layered polymer crystal region is obtained. After multiple salting-out and water-washing treatments, a hydrogel with high water content and high mechanical properties can be obtained. The water content is as high as 94.2wt%, the tensile strength is as high as 23.6±1.1MPa, the elongation at break is as high as 1278±90%, and the toughness in water is as high as 115.0±10.1MJ m -3 .

[0033] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0035] Figure 1 Comparison of tensile stress-strain curves of hydrogels with and without two-dimensional nanosheets in distilled water after one salting-out and water washing; the content of two-dimensional nanosheets is 0.58wt%;

[0036] Figure 2 Comparison of tensile stress and toughness of hydrogels with and without two-dimensional nanosheets in distilled water after one salting-out and water washing; the content of two-dimensional nanosheets is 0.58wt%;

[0037] Figure 3 Comparison of tensile stress-strain curves of hydrogels with and without two-dimensional nanosheets in seawater after one salting-out and water washing; the content of two-dimensional nanosheets is 0.58wt%;

[0038] Figure 4 DSC and crystallinity of hydrogels with and without nanosheets in distilled water after different times of salting out and washing; the content of two-dimensional nanosheets is 0.58wt%;

[0039] Figure 5 2DWAXS images of hydrogels without nanosheets A and with nanosheets B after five times of salting out and washing; the content of two-dimensional nanosheets is 0.58wt%;

[0040] Figure 6 TEM images of hydrogels without nanosheets A and with nanosheets B after five times of salting out and washing; the content of two-dimensional nanosheets is 0.58wt%;

[0041] Figure 7Comparison of tensile stress-strain curves of hydrogels in distilled water after different times of salting out and washing; the content of two-dimensional nanosheets is 0.58wt%;

[0042] Figure 8 Comparison of tensile stress-strain curves of hydrogels with different concentrations of two-dimensional nanosheets in distilled water after five-number salting-out and water washing. DETAILED DESCRIPTION

[0043] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0044] Hydrogels have good biocompatibility, high oxygen permeability, and elasticity, and have great application potential in tissue engineering, soft robotics, and smart actuators, such as controlled drug delivery systems, artificial biomedical scaffolds, and soft actuators.

[0045] All these practical applications require hydrogels to combine high water content and excellent mechanical properties in all directions. However, the mechanical strength of traditional hydrogels is generally poor, significantly lower than that of many natural biological tissues (such as tendons, ligaments and menisci). At the same time, they also lack the ordered and dynamic structure of biological soft tissues, which limits the widespread application of synthetic hydrogels.

[0046] Currently, the fabrication of strong, tough, and isotropic high-water-content hydrogels that are stable in different liquid environments remains an open problem.

[0047] To solve this problem, various methods have been tried to improve the mechanical properties of hydrogels, such as the double network method of changing the components; the ice template or directional freezing method of innovating the preparation method; the mechanical stretching method and salting-out method for post-processing of hydrogels.

[0048] However, these strategies do not significantly enhance the strength and fracture toughness of hydrogels, but only improve them in certain directions or enhance their performance by forming additional excess crystalline regions, which reduces their original high water content.

[0049] At present, the salting-out method controls the aggregation state of polymer segments in the hydrogel by adding specific ions. That is, under the action of specific ions, the mechanical properties of the prepared hydrogel are significantly improved due to the increase in the crystallinity of the polymer in the hydrogel. However, the mechanical properties of these hydrogels are significantly reduced after the salt is washed away, so that high water content and high strength and toughness cannot be achieved at the same time.

[0050] Therefore, it remains a major challenge to simultaneously fabricate isotropic, high-strength, and high-water-content hydrogels that are stable in different liquid environments.

[0051] In order to solve the above problems, the present invention proposes a high-strength and tough nanocomposite hydrogel, which contains polymers and two-dimensional nanosheets, wherein the polymers are distributed in any area of ​​the hydrogel, and the two-dimensional nanosheets are oriented and arranged in the hydrogel;

[0052] Among them, a nano-confined space is formed between adjacent two-dimensional nanosheets, and the nano-confined space contains layered PVA crystal regions.

[0053] Compared with the prior art, the present invention forms neatly arranged layered PVA crystal regions in the nano-confined space, and other parts are non-crystalline regions, so the water content of the hydrogel is improved. At the same time, the nano-confined space protects the crystal regions formed therein, so that the layered PVA crystal regions in the nano-confined space will not be destroyed by water, ensuring that the mechanical properties of the hydrogel are improved, and achieving a hydrogel with both high water content and high mechanical properties.

[0054] Specifically, the polymer includes polyvinyl alcohol and calcium alginate, and the total content of polyvinyl alcohol and calcium alginate is 80-99.9wt%.

[0055] Furthermore, when preparing the hydrogel, the calcium alginate is obtained by cross-linking sodium alginate and calcium ions.

[0056] Specifically, the two-dimensional nanosheets include graphene oxide or montmorillonite, and the content of the two-dimensional nanosheets is 0.1-20 wt %.

[0057] Exemplarily, the two-dimensional nanosheet is graphene oxide, wherein the content of graphene oxide is 0.24-1.9 wt %, and at this time, the total content of polyvinyl alcohol and calcium alginate is 98.1-99.76 wt %.

[0058] Exemplarily, the two-dimensional nanosheet is montmorillonite, wherein the content of montmorillonite is 0.1-20 wt %, and at this time, the total content of polyvinyl alcohol and calcium alginate is 80-99.9 wt %.

[0059] Among them, a small amount of polymers are gathered in the nano-confined space, and due to the low content of nanofillers, most of the polymers are located outside the nano-confined space.

[0060] Furthermore, super-spreading technology can be used to prepare hydrogels with nano-confined spaces.

[0061] Furthermore, the high-strength and tough nanocomposite hydrogel is obtained by salting out and washing the hydrogel with nano-confined space.

[0062] Specifically, the hydrogel with nano-confined space is subjected to salting-out treatment to cause the polymer to crystallize, and then the crystallized hydrogel is washed with water to destroy the crystalline region outside the nano-confined space. The nano-confined space protects the crystalline region formed inside it, so that the layered PVA crystalline region within the nano-confined space will not be destroyed.

[0063] Among them, during salting out, crystallization areas are generated anywhere in the hydrogel. Specifically, neatly arranged layered PVA crystallization areas are formed in the nano-confined space, while randomly arranged peripheral crystallization areas are formed in other parts.

[0064] Among them, after washing with water, the crystalline area outside the nano-confined space is destroyed, so the water content of the hydrogel is increased. At the same time, the nano-confined space protects the crystalline area formed inside it, so that the layered PVA crystalline area in the nano-confined space will not be destroyed, thereby obtaining a high-strength and tough nano-composite hydrogel with both high water content and high mechanical properties.

[0065] Furthermore, the number of times the hydrogel is salted out and washed with water is at least 2 times, and illustratively, the number of times the hydrogel is salted out and washed with water is 5 times.

[0066] Therefore, during the salting-out treatment, the present invention forms a crystallization region in any area of ​​the hydrogel, wherein neatly arranged layered PVA crystallization regions are formed in the nano-confined space, and randomly arranged peripheral crystallization regions are formed in other parts. After washing with water, the crystallization regions outside the nano-confined space are destroyed, the crystallinity of the hydrogel is reduced, and the water content is increased, while the layered PVA crystallization regions within the nano-confined space are not destroyed by washing with water. Compared with the randomly arranged peripheral crystallization regions, the mechanical properties of the hydrogel are ensured to be improved, thereby achieving a hydrogel with both high water content and high mechanical properties.

[0067] In addition, the present invention proposes a method for preparing a high-strength and tough nanocomposite hydrogel, comprising:

[0068] Step 1: preparing a hydrogel with nanoconfined space;

[0069] Step 2: salting out and washing the hydrogel to obtain a high-strength and tough nanocomposite hydrogel;

[0070] Among them, the hydrogel contains neatly arranged two-dimensional nanosheets, and nano-confined spaces are formed between adjacent nanosheets. After salting out and hydrolysis treatment, layered PVA crystal regions are formed in the nano-confined spaces.

[0071] Among them, the hydrogel contains polymers, and a small part of the polymers are gathered in the nano-confined space. During the salting-out treatment, the polymers crystallize to form crystalline regions. During the water washing treatment, the crystalline regions outside the nano-confined space are destroyed, and the layered PVA crystalline regions within the confined space are protected by the nano-confined space and are not destroyed.

[0072] Wherein, in step 1, a super-spreading technology can be used to prepare a hydrogel with nano-confined space, specifically, including:

[0073] S101: preparing an auxiliary forming hydrogel, and placing the prepared auxiliary forming hydrogel in water to swell to saturation;

[0074] S102: placing the auxiliary forming hydrogel swollen to saturation into a solution that is immiscible with the hydrogel;

[0075] S103: preparing a spreading solution, and continuously dropping the spreading solution onto the surface of the auxiliary forming hydrogel to perform super spreading and interfacial film-forming reaction, so as to obtain a hydrogel film on the surface of the auxiliary forming hydrogel;

[0076] S104: transferring the obtained hydrogel film to any solid surface, peeling it off from the solid surface after drying, and immersing it in water again to obtain a hydrogel.

[0077] Specifically, in step S101, polyacrylamide hydrogel is used as an auxiliary molding hydrogel to prepare polyacrylamide hydrogel by free radical polymerization, including: using acrylamide, N,N'-methylenebisacrylamide, ammonium persulfate and N,N,N',N'-tetramethylethylenediamine to polymerize in deionized water at room temperature to prepare polyacrylamide hydrogel.

[0078] Specifically, in step S102, the auxiliary forming hydrogel swollen to saturation is placed in a solution that is immiscible with the hydrogel; illustratively, the polyacrylamide hydrogel is immersed in a large amount of deionized water to remove unreacted monomers and fully swell.

[0079] Specifically, in step S103, the spreading solution is a mixed aqueous solution including two-dimensional nanosheets, polyvinyl alcohol (PVA), and sodium alginate (SA). The total content of polyvinyl alcohol and sodium alginate in the spreading solution is 80%-99.9wt%, and the ratio of polyvinyl alcohol to sodium alginate is 2-16:1, and an exemplary ratio of polyvinyl alcohol to sodium alginate is 16:1.

[0080] The components of the hydrogel include two-dimensional nanosheets, polyvinyl alcohol (PVA), and calcium alginate. Polyvinyl alcohol and calcium alginate exist in the hydrogel as polymers. When preparing the hydrogel film, calcium alginate is obtained by cross-linking sodium alginate with calcium ions.

[0081] Among them, two-dimensional nanosheets are used as nanofillers, and nanoconfined spaces are formed between the nanofillers. A small amount of polymers are gathered in the nanoconfined space, and due to the low content of nanofillers, most of the polymers are located outside the nanoconfined space. During salting out, crystallization regions are generated anywhere in the hydrogel, wherein neatly arranged layered PVA crystallization regions are formed in the nanoconfined space, and randomly arranged peripheral crystallization regions are formed in other parts. After washing, the crystallization regions outside the nanoconfined space are destroyed, so the water content of the hydrogel is increased. At the same time, the crystallization regions in the nanoconfined space will not be destroyed, which ensures that the mechanical properties of the hydrogel are improved compared to the randomly arranged peripheral crystallization regions.

[0082] Furthermore, the two-dimensional nanosheets may be graphene oxide (GO) or montmorillonite (MMT).

[0083] In a possible embodiment, the two-dimensional nanosheet is graphene oxide. In this case, the concentration of graphene oxide in the spreading solution is 0.24-1.9 wt %, and the total content of polyvinyl alcohol and sodium alginate is 98.1-99.76 wt %.

[0084] Exemplarily, the concentration of graphene oxide in the spreading solution is 0.58 wt %.

[0085] In a possible implementation, the two-dimensional nanosheet is montmorillonite. In this case, the concentration of montmorillonite in the spreading solution is 0.1-20 wt %, and the total content of polyvinyl alcohol and sodium alginate is 80-99.9 wt %.

[0086] Exemplarily, the concentration of montmorillonite in the spreading liquid is 1 wt %.

[0087] Wherein, in step S104, the solid may be a polytetrafluoroethylene film.

[0088] Among them, in step 2, the obtained hydrogel is immersed in a salt solution for salting out, and then immersed in deionized water to wash away the salt, and this step is repeated to obtain a high-strength and tough nano-composite hydrogel after multiple salting out and water washing.

[0089] Exemplarily, the salting-out and water-washing treatments are performed 5 times.

[0090] Furthermore, sodium citrate (SC) solution was used as a salt solution to salt out the hydrogel to induce the aggregation and crystallization of PVA, forming a dense polymer network and obtaining a strong hydrogel with isotropic mechanical properties.

[0091] The concentration of the sodium citrate solution is 0.5 to 1.5 mol / L, and illustratively, the concentration of the sodium citrate solution is 1.5 mol / L.

[0092] Compared with the prior art, the present invention uses two-dimensional nanosheets as nanofillers, adds a small amount of nanofillers into the hydrogel, forms nanoconfined spaces between the nanofillers, gathers a small amount of polymers in the nanoconfined spaces, and due to the low content of the nanofillers, most of the polymers are located outside the nanoconfined spaces. During salting out, a crystallization region is generated anywhere in the hydrogel, wherein neatly arranged layered PVA crystallization regions are formed in the nanoconfined spaces, and randomly arranged peripheral crystallization regions are formed in other parts. After washing, the crystallization regions outside the nanoconfined spaces are destroyed, so the water content of the hydrogel is increased. At the same time, the nanoconfined space protects the crystallization regions formed therein, so that the layered PVA crystallization regions in the nanoconfined space will not be destroyed. Compared with the randomly arranged peripheral crystallization regions, the mechanical properties of the hydrogel are ensured to be improved, thereby realizing the preparation of a hydrogel with both high water content and high mechanical properties.

[0093] The hydrogel is prepared using super-spreading technology, and a small amount of two-dimensional nanosheets are oriented and arranged in the hydrogel, forming a nano-confined space between adjacent two-dimensional nanosheets. During multiple salting-out and water-washing treatments, a layered PVA crystallization region is formed in the nano-confined space, and the nano-confined space is used to protect the crystallization region to avoid the water washing process from destroying the crystallization. At the same time, multiple salting-out treatments can achieve a superimposed improvement in crystallinity. During the multiple salting-out and water-washing treatments, the mechanical properties of the hydrogel are superimposedly increased.

[0094] Using two-dimensional nanosheets such as 0.58wt% graphene oxide, a hydrogel with neatly arranged nano-confined spaces was obtained. After five salting-out and water-washing treatments, a hydrogel with high water content and high mechanical properties was obtained. The water content was as high as 94.2wt%, the tensile strength was as high as 23.6±1.1MPa, the elongation at break was as high as 1278±90%, and the toughness in water was as high as 115.0±10.1MJ m -3 .

[0095] Example 1

[0096] A method for preparing a high-strength and tough nanocomposite hydrogel comprises:

[0097] Step 1: preparing a hydrogel with nanoconfined space;

[0098] Specifically, they include:

[0099] S101: preparing an auxiliary forming hydrogel, and placing the prepared auxiliary forming hydrogel in water to swell to saturation;

[0100] The method uses polyacrylamide hydrogel as auxiliary forming hydrogel and prepares polyacrylamide hydrogel through free radical polymerization, including:

[0101] 15 g acrylamide, 0.3 g N,N'-methylenebisacrylamide, and 0.3 g ammonium persulfate were dissolved in 100 mL deionized water and mixed evenly; then 300 μL N,N,N',N'-tetramethylethylenediamine was added, mixed evenly, poured into a reaction container, and polymerized at room temperature for 5 minutes to prepare polyacrylamide hydrogel.

[0102] S102: placing the auxiliary forming hydrogel swollen to saturation into a solution that is immiscible with the hydrogel;

[0103] Specifically, the polyacrylamide hydrogel is immersed in a large amount of deionized water to remove unreacted monomers and to fully swell the hydrogel.

[0104] The fully swollen hydrogel was taken out and cut into rectangles, each with a size of 10 cm × 10 cm. The rectangles were placed in a container and 200 mL of 1 M CaCl was added. 2 After soaking in the solution for one hour, take it out and place it on a clean glass plate.

[0105] S103: preparing a spreading solution, and continuously dropping the spreading solution onto the surface of the auxiliary forming hydrogel to perform super spreading and interfacial film-forming reaction, so as to obtain a hydrogel film on the surface of the auxiliary forming hydrogel;

[0106] The composition of the spreading solution is: GO (0.5wt%), PVA (Mw=130,000, 4wt%), SA (2wt%). Solutions with different GO contents can obtain hydrogel films with different mechanical properties, nanosheet orientation, and PVA crystallinity.

[0107] Among them, the concentration ratio of GO:PVA:SA is 0.58:93.57:5.85.

[0108] Specifically, the composition of the spreading solution was: 300 μl GO (0.5 wt%), 6000 μl PVA (Mw=130,000, 4 wt%), 750 μl SA (2 wt%) and 2700 μl deionized water.

[0109] The prepared reaction solution is continuously dripped onto the hydrogel surface. The sodium alginate in the solution will react with the calcium ions dissolved in the gel to form cross-links, and a hydrogel film can be obtained after about 1 minute.

[0110] S104: transferring the obtained hydrogel film to any solid surface, peeling it off from the solid surface after drying, and immersing it in water again to obtain a hydrogel.

[0111] Specifically, the nanofilm obtained by the reaction was transferred to a polytetrafluoroethylene membrane, and the GO / PVA / CA membrane was obtained after drying at room temperature for about 12 hours. The GO / PVA / CA dry membrane was obtained after peeling, and the GO / PVA / CA hydrogel was obtained by immersing it in water again.

[0112] Step 2: The hydrogel is subjected to salting-out and water washing treatment to obtain a high-strength and tough nanocomposite hydrogel.

[0113] Specifically, the obtained GO / PVA / CA hydrogel was immersed in a 1.5M sodium citrate aqueous solution for salting out for 1 hour to obtain a hydrogel after salting out, named SC-GO / PVA / CA hydrogel, and then the gel after salting out was immersed in an aqueous solution to wash away the salt.

[0114] 1-#01~#05 are the times of salting out and washing, which are 1, 3, 5, 7, and 9, respectively. The GO / PVA / CA hydrogels with different times of salting out and washing are obtained and named as (SC-H 2 O) 1 -GO / PVA / CA hydrogel, (SC-H 2 O) 3 -GO / PVA / CA hydrogel, (SC-H 2 O) 5 -GO / PVA / CA hydrogel, (SC-H 2 O) 7 -GO / PVA / CA hydrogel, (SC-H 2 O) 9 -GO / PVA / CA hydrogel.

[0115] Example 2

[0116] The difference from Example 1 is the composition of the spreading liquid.

[0117] Specifically, the spreading solution includes GO (0.5 wt %), PVA (Mw=130,000, 4 wt %), and SA (2 wt %).

[0118] Among them, 2-#01~#04 are hydrogels prepared with different graphene oxide contents. Specifically, in the spreading liquid, the concentrations of graphene oxide are 0, 0.24wt%, 0.58wt%, and 1.9wt%, respectively, and the PVA:SA concentration ratio is always 16:1.

[0119] Salting out and washing with water were performed 5 times.

[0120] Example 3

[0121] The difference from Example 1 is that the spreading liquid consists of MMT (2 wt %), PVA (Mw=130,000, 4 wt %), SA (2 wt %) and deionized water.

[0122] Among them, the concentration ratio of MMT:PVA:SA is: 1:93.18:5.82.

[0123] The composition of the spreading solution was 46 μl MMT (2 wt%), 2000 μl PVA (M w =130,000, 4 wt%), 250 μl SA (2 wt%) and 954 μl deionized water.

[0124] Salting out once.

[0125] Comparative Example 1

[0126] A hydrogel, which is different from Example 1 in that the hydrogel contains non-uniformly distributed and agglomerated graphene oxide.

[0127] Specifically, the preparation method includes: using the same uniform reaction solution, utilizing a conventional casting method, that is, pouring the reaction solution directly into a 10 cm×10 cm mold, and drying in air to prepare a GO / PVA / CA composite hydrogel.

[0128] The composition of the hydrogel is specifically: 300 μl GO (0.5 wt%), 6000 μl PVA (Mw=130,000, 4 wt%), 750 μl SA (2 wt%) and 2700 μl deionized water.

[0129] Salt out and wash with water once.

[0130] Comparative Example 2

[0131] A hydrogel, which differs from Example 1 in the composition of the spreading liquid.

[0132] Specifically, the spreading solution includes 2000 μl PVA (Mw=130,000, 4 wt%) and 250 μl SA (2 wt%).

[0133] Salt out and wash with water once.

[0134] The hydrogels obtained in Examples 1-3 and Comparative Examples 1-2 were tested, and the results are shown in Table 1 below:

[0135] Table 1 Water content, tensile strength, elongation at break and toughness of hydrogels in water

[0136] Example Water content (wt%) Tensile strength(MPa) Elongation at break (%) <![CDATA[Toughness (MJ m -3 )]]> 1-#01 94.6 7.5±0.5 1104±98 37.2±3.4 1-#02 94.3 12.2±0.6 970±75 52.1±4.9 1-#03 94.2 23.6±1.1 1278±90 115.0±10.1 1-#04 92.4 22.7±1.2 1222±81 114.7±10.5 1-#05 92.1 23.4±1.5 1168±68 105.9±9.7 2-#01 95.5 6.5±0.3 854±51 25.0±2.2 2-#02 95.1 16.4±0.8 1655±110 104.0±9.2 2-#03 94.2 23.6±1.1 1278±90 115.0±10.1 2-#04 87.2 18.7±0.9 858±54 74.9±7.2 Example 3 53.5 66.1±2.2 857±37 293.8±27.8 Comparative Example 1 93.2 2.1±0.2 1071±82 8.2±0.6 Comparative Example 2 95.8 0.52±0.03 573±48 0.60±0.05

[0137] The specific analysis is as follows:

[0138] 1. Comparison of tensile stress-strain curves of hydrogels in distilled water for 1-#01 and comparative example 2. Figure 1As shown, it can be seen that in distilled water, the tensile stress of the hydrogel containing neatly arranged two-dimensional nanosheets is significantly improved.

[0139] 2. Comparison of tensile stress and toughness of hydrogel in distilled water for 1-#01 and comparative example 2: Figure 2 As shown, it can be seen that in distilled water, the tensile stress and toughness of the hydrogel containing neatly arranged two-dimensional nanosheets are significantly improved.

[0140] 3. Comparison of tensile stress-strain curves of hydrogels in seawater for 1-#01 and comparative example 2 Figure 3 As shown, it can be seen that in seawater, the tensile stress of the hydrogel containing neatly arranged two-dimensional nanosheets is significantly increased.

[0141] 4. For 1-#01~#05, 2-#01 and Comparative Example 2, the DSC curves and crystallinity of the hydrogels are as follows: Figure 4 As shown in Figure 2, with the increase of salting-out times, (SC-H 2 O) 5 -GO / PVA / CA hydrogel has improved crystallinity, but it is lower than the crystallinity of hydrogel without nanosheets with the same number of salting-out times, that is, there are neatly arranged crystal regions in hydrogel with nanosheets, while there are disorderly arranged crystal regions in hydrogel without nanosheets. From the perspective of crystallinity, hydrogel without nanosheets has higher crystallinity, but its mechanical properties are much lower than those of hydrogel with nanosheets.

[0142] It can be seen that the neatly arranged layered crystal regions improve the mechanical properties of the hydrogel compared to the randomly arranged peripheral crystal regions.

[0143] 5. For 1-#03 and 2-#03, the 2D WAXS images of the hydrogels are as follows: Figure 5 As shown, it can be seen that in the hydrogel containing nanosheets, the degree of polymer orientation is higher, and layered PVA crystal regions are formed between the neatly arranged nanosheets.

[0144] 6. For 1-#03 and 2-#03, the TEM images of the hydrogels are as follows: Figure 6 As shown, it can be seen that the crystals in the hydrogel containing two-dimensional nanosheets are arranged neatly, while the hydrogel without two-dimensional nanosheets is arranged randomly.

[0145] 7. Comparison of tensile stress-strain curves of hydrogels in distilled water for 1-#01~#05 and 2-#01~#04. Figure 7-8 As shown, it can be seen that the optimal graphene oxide concentration is 0.58wt% and the number of salting-out and washing times is 5.

[0146] In summary, the present invention achieves highly ordered arrangement of nanosheets at the immiscible gel / oil interface by utilizing shear flow force. Well-oriented layered nanosheets help to form neatly arranged layered PVA crystal regions during multiple salting-out processes. The prepared composite hydrogel has a tensile strength of up to 23.6±2.1MPa, an elongation at break of 1278±107%, and a toughness of 115.0±9.8MJ m -3 , and its water content can reach 90-95%, and its comprehensive mechanical properties exceed all previously reported hydrogel materials. Therefore, the isotropic composite hydrogel with high strength and toughness is prepared by using the super-spreading assisted multiple salting-out treatment method.

[0147] Furthermore, this strategy can be extended to other nanosheets and polymers, which provides a general and efficient route for the continuous fabrication of advanced nanocomposite gel materials for practical applications.

[0148] Those skilled in the art will appreciate that all or part of the processes of the above-mentioned embodiments can be implemented by instructing related hardware through a computer program, and the program can be stored in a computer-readable storage medium, wherein the computer-readable storage medium is a disk, an optical disk, a read-only storage memory, or a random access memory, etc.

[0149] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A high-strength and tough nanocomposite hydrogel, characterized in that: The hydrogel contains polymers and two-dimensional nanosheets, the polymers are distributed in any area of ​​the hydrogel, and the two-dimensional nanosheets are oriented and arranged in the hydrogel; Wherein, a nano-confined space is formed between adjacent two-dimensional nanosheets, and a layered PVA crystal region is contained in the nano-confined space; The method for preparing the high-strength and tough nanocomposite hydrogel comprises: Step 1: preparing a hydrogel with nano-confined space; said step 1 comprises: S101: preparing an auxiliary forming hydrogel, and placing the auxiliary forming hydrogel in water to swell to saturation; S102: placing the auxiliary forming hydrogel swollen to saturation into a solution that is immiscible with the hydrogel; S103: preparing a spreading solution, and continuously dropping the spreading solution onto the surface of the auxiliary forming hydrogel to perform super spreading and interfacial film-forming reaction, so as to obtain a hydrogel film on the surface of the auxiliary forming hydrogel; the spreading solution is a mixed aqueous solution comprising two-dimensional nanosheets, polyvinyl alcohol, and sodium alginate; wherein the two-dimensional nanosheets comprise graphene oxide or montmorillonite, and the content of the two-dimensional nanosheets in the spreading solution is 0.1-20wt%; the total content of the polyvinyl alcohol and sodium alginate in the spreading solution is 80%-99.9wt%; the ratio of polyvinyl alcohol to sodium alginate is 2-16:1; S104: transferring the hydrogel film to a solid surface, peeling it off from the solid surface after drying, and immersing it in water again to obtain a hydrogel with nano-confined space; Step 2: The hydrogel is subjected to salting-out and water washing treatment to obtain a high-strength and tough nanocomposite hydrogel; wherein the hydrogel contains neatly arranged two-dimensional nanosheets, and nano-confined spaces are formed between adjacent two-dimensional nanosheets. After salting-out and hydrolysis treatment, a hydrogel containing layered PVA crystal regions in the nano-confined spaces is obtained.

2. A method for preparing the high-strength and tough nanocomposite hydrogel according to claim 1, characterized in that: include: Step 1: preparing a hydrogel with nanoconfined space; The step 1 includes: S101: preparing an auxiliary forming hydrogel, and placing the auxiliary forming hydrogel in water to swell to saturation; S102: placing the auxiliary forming hydrogel swollen to saturation into a solution that is immiscible with the hydrogel; S103: preparing a spreading solution, and continuously dropping the spreading solution onto the surface of the auxiliary forming hydrogel to perform super spreading and interfacial film-forming reaction, so as to obtain a hydrogel film on the surface of the auxiliary forming hydrogel; the spreading solution is a mixed aqueous solution comprising two-dimensional nanosheets, polyvinyl alcohol, and sodium alginate; wherein the two-dimensional nanosheets comprise graphene oxide or montmorillonite, and the content of the two-dimensional nanosheets in the spreading solution is 0.1-20wt%; the total content of the polyvinyl alcohol and sodium alginate in the spreading solution is 80%-99.9wt%; the ratio of polyvinyl alcohol to sodium alginate is 2-16:1; S104: transferring the hydrogel film to a solid surface, peeling it off from the solid surface after drying, and immersing it in water again to obtain a hydrogel with nano-confined space; Step 2: salting out and washing the hydrogel to obtain a high-strength and high-toughness nanocomposite hydrogel; The hydrogel contains neatly arranged two-dimensional nanosheets, and nano-confined spaces are formed between adjacent two-dimensional nanosheets. After salting out and hydrolysis treatment, a hydrogel containing layered PVA crystal regions in the nano-confined spaces is obtained.

3. The method according to claim 2, characterized in that: When the hydrogel having nano-confined space is subjected to salting-out treatment, the polymer crystallizes; Wherein, a layered PVA crystal region is formed in the nano-confined space, and a randomly arranged peripheral crystal region is formed outside the nano-confined space.

4. The method according to claim 3, characterized in that: When the hydrogel after salting out is washed with water, the PVA crystal region within the nano-confined space is not destroyed, and the peripheral crystal region outside the nano-confined space is destroyed.

5. The method according to claim 2, characterized in that: The spreading solution is a mixed aqueous solution including two-dimensional nanosheets, polyvinyl alcohol, and sodium alginate; Wherein, the two-dimensional nanosheets include graphene oxide, and the content of the graphene oxide in the spreading liquid is 0.24-1.9wt%; the total content of the polyvinyl alcohol and sodium alginate in the spreading liquid is 98.1-99.76wt%; or the two-dimensional nanosheets include montmorillonite, the concentration of the montmorillonite in the spreading liquid is 0.1-20wt%, and the total content of the polyvinyl alcohol and sodium alginate is 80-99.9wt%; The ratio of polyvinyl alcohol to sodium alginate is 2-16:

1.

6. The method according to claim 5, characterized in that: The two-dimensional nanosheet is graphene oxide, and the content of the graphene oxide in the spreading solution is 0.58 wt %.

7. The method according to claim 2, characterized in that: In step 2, the hydrogel is immersed in a salt solution for salting out, and then immersed in deionized water to wash away the salt. The steps of immersing in a salt solution and then immersing in deionized water to wash away the salt are repeated to obtain a high-strength and tough nanocomposite hydrogel.

8. The method according to claim 7, characterized in that: In the step 2, the hydrogel is subjected to salting out and water washing for 5 times.

Citation Information

Patent Citations

  • Preparing method of biomimetic laminated high-strength composite hydrogel film

    CN102604302A

  • Method and device for continuously preparing functional high-molecular membrane in large areas

    CN108929449A